Reduksi Waktu Set up Pekerjaan Penggantian Ban Sepeda Motor dengan Metode Single Minute Exchange of Dies - Indra Rizki Pratama; Fredy Sumasto; Febriza Imansuri; B. Handoko Purwojatmiko (Fakultas Teknik, 2023)
Currently, almost every household in Indonesia has a motorbike, this is certainly a business opportunity. One of the most important components of a motorbike is the tire which functions to reduce vibration and protect the wheel from wear and damage. The business environment operating in the automotive sector needs to create high-quality goods or services to increase customer satisfaction. Costs in the company's productive processes must be reduced to achieve effectiveness. The object of this research is the XYZ Tire Workshop located in East Jakarta. In a day, the XYZ Ban workshop can provide up to 25 to 30 motorbike tire changes. Meanwhile, the workforce on duty is only 2 mechanics and the quantity of tools is limited. This causes delays and makes customers have to wait quite a long time before their motorbike can be worked on. The Single Minute Exchange of Dies (SMED) method which is included in lean tools is the key to reducing set-up process time. In general, SMED aims to standardize and simplify operating processes. The SMED technique is used as an element in Total Productivity Maintenance (TPM) in various studies to achieve lean manufacturing. Based on research data, the set-up time before implementing SMED was 177 seconds. After implementing the SMED method, the setup time was 126 seconds. This shows that the SMED method can reduce set-up time by 51 seconds.